Respecting entitlements in legislative bargaining - A matter of preference or necessity? - Anita Gantner; Regine Oexl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
In division problems with entitlements, we investigate whether fairness concerns overrule strategic behavior and inhibit full use of the decision-making power. In a lab experiment where entitlements are derived from costly contributions, we vary bargaining power by using either the majority rule or the dictator rule to find a division allocation. We apply very coarse measures for assessing whether entitlements are respected under both rules. For inexperienced subjects, we find a large number of proposals in which all partners receive positive amounts. With experience, however, over one third of proposers leave at most the crumbs for both partners (dictator) or one of them (majority bargaining). Past individual observations of such 'extreme' outcomes increase the likelihood of own 'extreme' proposals not only under the majority rule, but also under the dictator rule, where no learning of strategic behavior is expected. In heterogeneous groups, where partners bring in different contributions, about 50% of proposals do not reflect an ordinal comparison of the partners' entitlements. Overall, this shows significant limits in people's preferences for fairness.
Keywords: C91; D01; 330; majority bargaining; dictator game; entitlements